Pengaruh Penggunaan Internet Terhadap Keterampilan Literasi Informasi Masyarakat Di Kelurahan Balai-Balai Kota Padang Panjang - Rezzy Febriola; Malta Nelisa (Pusat Riset dan Inovasi Nasional, 2024)
The purpose of this research is to describe (1) the diversity of people's internet use in the Balai-Balai Kota Padang Panjang subdistrict, (2) the information literacy skills of the community in the Balai-Balai Kota Padang Panjang subdistrict, (3) the influence of internet use on the information literacy skills of the community in Padang Panjang City Hall sub-district. This research uses quantitative research with descriptive methods. The population in this study was the community in the Balai-Balai City District of Padang Panjang with sampling using simple random sampling. The main instrument used was a research questionnaire which had been tested for validity and reliability, the sample size was 98 people. The population in the study was the community in the Balai-Balai City District of Padang Panjang. Data collection techniques are questionnaire techniques and questionnaire data processing through editing and tabulation stages. The results of the research are: (1) The community's internet use has an average answer score of 3.21. This score is on an interval scale of 2.50 – 3.24, which means that the internet use of the Padang Panjang City Hall community is classified as good. This can be seen from the intensity, usefulness and effectiveness of internet use carried out well. (2) Public information literacy has an average answer score of 3.11. This score is on an interval scale of 2.50 – 3.24, which means that the information literacy of the Padang Panjang City Hall community is classified as good. This can be seen from information literacy skills in determining information needs, finding information, evaluating information and using information for certain purposes by understanding aspects that are considered good. (3) The influence of internet use on the information literacy skills of people in the Balai-Balai City District of Padang Panjang is strong. From the results of the SPSS regression test, a correlation coefficient value of R = 0.787 was obtained, meaning that internet users have a positive influence on information literacy skills. The higher the use of the internet, the higher the information literacy skills in the Balai-Balai City District of Padang Panjang.